Pengaruh Dissimilar Welding (MIL-DTL-46100 dan ISO-15608 1.2) Terhadap Sifat Mekanik Sambungan Las pada Kendaraan Tempur - Yunika, Syaloom; Aritonang, Sovian; Helmy, Rizky Kurnia (Fakultas Teknik UMSU, 2024)
Material testing before use in combat vehicles is critical. The aim is to detect and resolve defects in combat vehicle materials so that the vehicle can operate optimally. This research aims to improve the structural performance of combat vehicles by focusing on dissimilar welding material testing. The materials observed in this study were MIL-DTL 46100 Armor and ISO-15608 1.2 Non-Armor, which were evaluated through metallographic analysis (to examine microstructure) and Vickers Microhardness testing (to assess hardness). This was done to ensure that the materials used in combat vehicles can effectively deal with various threats. Results showed that metallographic observation of the HAZ of the three specimens revealed that the microstructure was dominated by acicular ferrite. This structure is highly desirable in welding joints. Generally, the non-armor material (ISO-15608 1.2) has a lower range of HV values than the armor material (MIL-DTL-46100). This indicates that the armor material has a higher hardness, which suits the needs of protection applications.